ВПЛИВ ЄВРОПЕЙСЬКОЇ ОСВІТНЬОЇ ПОЛІТИКИ НА ФОРМУВАННЯ ВИЩОЇ ОСВІТИ У ВЕЛИКІЙ БРИТАНІЇ - Mudryi, Yaroslav; Mudra, Olena (Дрогобицький державний педагогічний університет імені Івана Франка, 2022)
This article is on characteristics of the higher education system of Great Britain, its reform, as well as the characteristics and feasibility of innovations. It is proved that educational policy has an impact on the formation of higher education in the European Union. The conditions for the implementation of the general educational strategy for the development of higher education through the implementation of internal and external educational programs, adaptation of qualification levels and assessment systems, initiating deepening international relations, promoting monitoring and evaluation of national indicators, exchange of experience, support for democratic education policy. Analysis of European educational policy, its institutional structure and role in shaping higher education in the UK, identifying features of educational strategy is of interest for our study in the context of national strategic orientation to foreign language education, approaching its economic, educational and social standards. That is why we conducted a detailed analysis of certain educational regulations in the UK to determine the level of influence of European education policy on the formation of higher education in the country. The conducted scientific research on the reform of education in higher education institutions in Great Britain gives grounds to claim that at the end of the twentieth century thanks to numerous and far-reaching reforms actively implemented by the British government, the British higher education system has acquired signs of structure, centralization and hierarchy. Reforming the higher education system became possible only when the reform became systematic and at the same time affected teaching methods, the quality of curricula and textbooks, changed the views and perceptions of teachers on the learning process. In the process of research we have identified the main characteristics of higher education in the UK, analyzed the reform of education in recent years. We have also identified key documents in the field of education that have contributed to the effective development of higher education and improved the training of specialists; the process of education reform and the problems that arose in it are considered and analyzed in detail; possible joint development of higher education in Great Britain and Ukraine is proposed.
THE INFLUENCE OF EUROPEAN EDUCATIONAL POLICY ON THE FORMATION OF HIGHER EDUCATION IN THE UNITED KINGDOM
Keywords: вища освіта; професійна підготовка фахівців; реформи вищої освіти; Болонський процес; Європейський простір вищої освіти; євроінтеграція; Велика Британія; higher education; professional training; higher education reforms; the Bologna Process; the European Higher Education Area; European integration; Great Britain